Non-contrast-enhanced MR hepatic arteriography with time-spatial labeling inversion pulses: comparison of imaging with flow-in and modified flow-out methods. (July 2017) - Isoda, Hiroyoshi; Furuta, Akihiro; Ohno, Tsuyoshi; Togashi, Kaori
Background: In non-contrast-enhanced magnetic resonance (MR) arteriography, the flow-out method using a selective tagging pulse with a long inversion time (TI) and a non-selective inversion recovery pulse with a short TI (the modified flow-out method) might further contribute to the suppression of background signal and facilitate improved visualization of the hepatic artery. However, no report has focused on the image quality of non-contrast-enhanced MR arteriography using the modified flow-out method. Purpose: To compare the flow-in method with the modified flow-out method and to determine which method better visualizes the hepatic artery. Material and Methods: Twenty-seven healthy volunteers were examined using respiratory-triggered three-dimensional true steady-state free-precession MR with two selective inversion recovery pulses (the flow-in method) or with one tagging pulse and one non-selective inversion recovery pulse (the modified flow-out method). Results: Artery-to-liver contrast was signiﬁcantly increased in the modified flow-out method relative to the flow-in method ( P < 0.05). In all analyses of vessel visibility, non-contrast-enhanced MR arteriography using the modified flow-out method exhibited higher scores than with the flow-in method. With respect to overall image quality, the modified flow-out method was signiﬁcantly better than the flow-in method ( P < 0.01). Conclusion: The modified flow-out method for non-contrast-enhanced MR angiography is a promising technique for visualizing the hepatic artery.